Emergencant surgical coronary revascularization in patients with acute myocardial infarction - A. G. Bitsadze; M. F. Rotar; B. М. Todurov (Ukrainian Journal of Cardiovascular Surgery, 2017)
Coronary heart disease (IHD) is the most common cause of death worldwide. Acute myocardial infarction (AMI) is the most severe complication of IHD, which is result of acute or progressive heart failure or severe rhythm disorderss. The most frequent and immediate cause of death of patients with MI is a ventricular fibrillation.In recent years, optimization of perioperative management, including the myocardial protection, has led to acceptable results in emergency surgical myocardial revascularization, even in patients with cardiogenic shock. Today, emergency coronary artery bypass grafting (CABG) is no longer considered as an operation of desperation.Materials and methods. Between January 2011 and August 2016, 187 patients with acute myocardial infarction (42 – 22.5%) without ST-segment elevation (NSTEMI), 145 (77.5%) with ST-segment elevation (STEMI) were urgently operated at the «Heart Institute» of the Ministry of Health of Ukraine. In all cases, the values of troponin I were positive, all patients underwent an emergency coronary bypass within 6 hours after coronary angiography.In the prevailing majority of patients (155/83%), coronary bypass surgery was performed using a noncardiaplegic technique, i.e., artificial heart fibrillation with intermittent aortic clamping and moderate hypothermia (28.5±0.5 °С). In 32 (17%) patients, CABG was performed on a working heart. The combination of the left internal thoracic artery and venous shunts for revascularization was used only in hemodynamically stable patients (29/15.6%).Results. In the most cases, we used venous grafts for CABG. In 32 patients with stable hemodynamics, the left anterior descending artery was bypassed by the left internal thoracic artery. In 103 (55%) patients, intracoronary shunts were used in the imposition of distal anastomoses. Complete revascularization (shunted at least 3 arteries) was achieved in 152 (81.2%) patients. In 32 (17.1%) patients, stents were implanted in the pre-operative stage in the infarct-dependent artery, but due to the ineffectiveness of this procedure, the patients were operated on. The total number of shunts per patient was 2.7±0.4. The mean duration of the artificial circulation was 61±2.6 min. Hospital mortality in the presented group of patients was 12.2% (23 patients died, all with ST-segment elevation).